191 THE RESPONSE OF MRL/LPR-INDUCIBLE NITRIC OXIDE SYNTHASE KNOCKOUT MICE TO INDUCIBLE NITRIC OXIDE SYNTHASE INHIBITOR. Issue 1 (1st January 2007) - Njoku, C. J.; Gilkeson, G. S.; Hofbauer, A.; Ruiz, P.; Oates, J. C.
Abstract : Increases in systemic nitric oxide (NO) production are associated with disease progression, and pharmacologic inhibition of inducible nitric oxide synthase (iNOS) abrogates disease in the MRL/lpr murine model of lupus. However, genetic manipulation of iNOS alone does not improve inflammatory glomerular or joint disease in these mice. We hypothesize that the arginine analog iNOS inhibitors used either had non-iNOS-mediated effects or they inhibit potentially pathogenic activity in other NOS isoforms as well. To address these hypotheses, 21 mice (either iNOS −/− mutants or iNOS +/+ littermates) on the MRL/lpr background were divided into three groups: (1) seven iNOS +/+ littermates given placebo, (2) seven iNOS −/− mice given placebo, and (3) seven iNOS −/− mice given an iNOS inhibitor (SC-51) by subcutaneous sustained release pellet, given between ages 10 and 24 weeks of age. Urine nitrate + nitrite (NOX in μmol/mouse/d) and albumin (μg/mouse/d) levels were measured biweekly. Mice were sacrificed at 24 weeks, and the kidneys were sectioned, stained, and scored for glomerular pathology by light microscopy. NOX levels were greatest among the wild-type littermates (1.7 ± 1.5) than either of the knockout groups ( p < .001), whereas iNOS inhibitor therapy did not affect urine NOX levels among the iNOS −/− mice given either placebo (0.5 ± 0.3) or SC-51 (0.5 ± 0.3). SC-51 significantly prevented the age-related rise in urine albumin seen in the placebo-treated iNOS −/− mice and the iNOS +/+ littermates given placebo at 22, 24, and 25 weeks of age ( p < .05 for each time point). Glomerular pathologic scores were the same in all groups. Taken together, these data suggest that there were non-iNOS-mediated effects of SC-51 on glomerular permeability but not on glomerular inflammation as measured by light microscopy. Other NOS isoforms (endothelial and neuronal NOS), known to produce both NO and superoxide, may have been inhibited by SC-51 and may affect glomerular filtration of proteins via several mechanisms. Reactive intermediates produced by NOS isoforms could have changed the glomerular basement membrane size and charge barrier. If SC-51 also inhibited eNOS or nNOS, it may have reduced glomerular hydrostatic pressure. Future experiments will investigate the effects of iNOS therapy on systemic reactive oxygen production, glomerular electron microscopic findings, and the urine proteome in this mouse model.